The Influence of Ease of Navigation, Mobile Shopping Experience, and Social Commerce Engagement on Omnichannel Customer Experience of Local Brand Products in E-Commerce - Sidjabat, Sonya; Mustafa, Fahrina; Suhara, Ade; Susilowati, Tri; Violin, Vivid; Primananda, Pande Gde Bagus Naya (Journal of Social Science and Business Studies, 2026)
Local brands establish unified customer experiences through their omnichannel system implementation because e-commerce competition has increased in intensity. The research investigates how three variables which each contain three elements affect omnichannel customer experience for local brand products in e-commerce through their three elements which include ease of navigation and mobile shopping experience and social commerce engagement. The researchers implemented their study through a quantitative research method which employed explanatory research design. The researchers used purposeful sampling methods to collect data from 200 participants who had purchased local brand products through multiple digital channels. The researchers applied multiple linear regression analysis to their data after they conducted validity and reliability testing along with classical assumption testing. The study results demonstrate that three factors which include website navigation skills and mobile shopping experience and social commerce platform usage enable users to access various shopping channels. The complete customer experience development process requires businesses to comprehend how platform experience integrates with mobile user experience and social media interaction. The research contributes to digital marketing and omnichannel studies by providing new theoretical insights. The study results provide local brands with digital strategy development guidelines which focus on enhancing customer experience.